Use of Game Therapy in Preschool Educational Organizations - Nematullayeva Sarvinoz Khushvakht kizi (Genius Publishing Group, 2022)
This article discusses the use of home therapy in preschool education. Play therapy is a method of correcting emotional and behavioral disorders in children from 2 to 7 years old, which is based on the child's way of interacting with the outside world - a game. Play is to a child what speech is to an adult. In the process of play therapy, personal relationships are created between group members, due to which tension and fear of other people are relieved, self-esteem increases
Keywords: Preschool education; home therapy; thinking; health